MERDEKA EKSPOR-UMKM MERDEKA : KOLABORASI STAKEHOLDERS DAN SKEMA BISNIS UMKM EKSPOR DI MASA PEMULIHAN EKONOMI - Ardianto, Heni; Asngadi, Asngadi (Universitas Prof. Dr. Hazairin SH, 2022)
This study aims to formulate strategic steps in the form of collaboration models and businessschemes through collaboration between interested parties in providing export space forMSMEs so that they can make independent MSMEs to survive and compete in the economicrecovery period. The research is conducted with a qualitative approach to find models orconcepts that can be used to deal with export opportunities. Data were analyzed descriptivelybased on data obtained through reading materials consisting of various literatures to obtainrelevant secondary data. The results show that collaboration between stakeholders areexpected to be a model that can strengthen the competitiveness of MSMEs in the global(export) market. Entrepreneurs must be equipped with knowledge related to exportopportunities through onboarding business schemes such as coaching, empowerment,licensing management, certification to curation to survive and rise and compete in the globalmarket. This of course needs to be realized with good synergy between stakeholders so thatthe transformation process can run well. In addition, the government as the coordinator mustbe able to synergize with other stakeholders actively to discuss developments as a form ofcoordination and material for continuous evaluation.